2019
DOI: 10.1001/jamanetworkopen.2019.16205
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Acute Gastroenteritis and Continuous Use of Proton Pump Inhibitors During Winter Periods of Highest Circulation of Enteric Viruses

Abstract: IMPORTANCE An increased risk of acute bacterial enteric infections has been reported among patients receiving proton pump inhibitor (PPI) therapy. The risk of acute gastroenteritis (AGE) of viral origin associated with continuous PPI exposure has been less studied. OBJECTIVE To investigate the association between continuous PPI therapy and AGE occurrence during winter epidemic periods when the circulation of enteric viruses is the highest. DESIGN, SETTING, AND PARTICIPANTS A matched cohort study was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…5 These results align with those of previous studies 7,8 that identified associations between PPI use and incidence of specific enteric illnesses, including those caused by Clostridium difficile and norovirus (a prominent pathogen associated with AGE). 5 Although Vilcu et al 5 thoroughly address limitations of their study, including outcome ascertainment using drug dispensing data and confounding by indication, it is important to reiterate that the possibilities of residual confounding and protopathic bias remain, particularly because adjustment for comorbidities relied on drug dispensation information alone. In the study, as is common in many settings, patients receiving long-term PPI treatment were significantly sicker than non-PPI users.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…5 These results align with those of previous studies 7,8 that identified associations between PPI use and incidence of specific enteric illnesses, including those caused by Clostridium difficile and norovirus (a prominent pathogen associated with AGE). 5 Although Vilcu et al 5 thoroughly address limitations of their study, including outcome ascertainment using drug dispensing data and confounding by indication, it is important to reiterate that the possibilities of residual confounding and protopathic bias remain, particularly because adjustment for comorbidities relied on drug dispensation information alone. In the study, as is common in many settings, patients receiving long-term PPI treatment were significantly sicker than non-PPI users.…”
supporting
confidence: 90%
“…1 Although PPIs are considered safe overall, they have now been linked to numerous adverse events, including drug-drug interactions, hypomagnesemia, osteoporotic fractures, and serious infections. 1 The study by Vilcu and colleagues 5 investigates an emerging concern of infectious complications associated with persistent PPI use: increased risk of acute gastroenteritis (AGE) during AGE epidemics.…”
mentioning
confidence: 99%
See 3 more Smart Citations